Weak Labeling-specific Emitter Identification Algorithm Based on the Weakly Supervised Wav-KAN Network - Kangsheng LIU; Qing LING; Wenjun YAN; Limin ZHANG; Keyuan YU; Hengyan LIU (Leida xuebao)
Most existing specific emitter identification technologies rely on supervised learning, making them unsuitable for scenarios with label loss due to factors such as the acquisition environment (e.g., weather conditions, terrain, obstacles, and interference sources), device performance (e.g., radar resolution, signal processing capabilities, and hardware failures), and tagger level. In this study, a weakly labeled specific emitter identification algorithm based on the Weakly Supervised Wav-KAN (WSW-KAN) network is proposed. First, a WSW-KAN baseline network is constructed by integrating the unique learnable edge function of the KAN network with the multiresolution analysis of the wavelet function. The weakly labeled dataset is then divided into a small labeled dataset and a large unlabeled dataset, with the small labeled dataset used for initial model training. Finally, based on the pretrained model, Adaptive Pseudo-Label Weighted Selection (APLWS) is used to extract features from the unlabeled data using a contrast learning method, followed by iterative training, thereby effectively improving the generalization capability of the model. Experimental validation using a real acquisition radar dataset demonstrates that the proposed algorithm achieves a recognition accuracy of approximately 95% for specific emitters while maintaining high efficiency, a small parameter scale, and strong adaptability, making it suitable for practical applications.